Adherence to Antiretroviral Medicines among Adult Hiv/Aids Patients at the Korle Bu Teaching Hospital in Accra, Ghana. - Ocansey, D (University of Ghana, 2009)
It is very important to assess adherence to ARTs to understand why treatment fail. However, measurement of adherence especially in the clinic setting is very difficult as there is no single method that best measures it. The main objective of this study was to measure adherence to ART among HIV patients (PLWHA) at the Korle Bu Teaching Hospital (KBTH) using, pill counts and Self-report and also to identify factors that contributes to optimal adherence. The design was a cross sectional descriptive study which used systematic sampling to collect quantitative and qualitative data from adult ARV users who have been on ARTs for at least three months and attended clinic between May and July 2009. A t-test was performed to compare mean adherence and Multivariate logistic regression was used to determine factors that were associated with adherence. Analysis included 229 patients. Of the three methods used, optimal adherence rate (≥95%) was highest for 7- day recall (100%), followed by three-month pill count method (98%), and three-month visual line self report recorded the least adherence rate (77%). Overall rate of adherence was found to be 92%. This is higher than what some studies in developing countries have found. However, the overall adherence was below the minimum expected adherence of 95% which experts in ART management recommend. Three month pill count recorded high optimal adherence compared to a visual line self report optimal adherence which was low but matched results from most African countries. Pill count method of measuring adherence should be used routinely to monitor patients on ARTs while self reported adherence should be used to identify patients who need extra support for adherence. Quality of care was found to be a factor that contributes to optimal adherence, a finding that was also buttressed during the qualitative study.
Thesis (MpH) - University of Ghana,2009
Keywords: Antiretroviral Medicines; Korle Bu; Hiv/Aids